Attributes of sawn timber important for the manufacturers of value-added wood products in Malaysia - Ratnasingam, Jegatheswaran; Lim, Choon Liat; Ramasamy, Geetha; Mohamed, Shukri; Senin, Abdul Latib (North Carolina State University, 2016)
The objective of this study was to assess the attributes of selected sawn timber species for door, flooring, and furniture manufacturing in Malaysia. Sawn timber attributes are important for value-added wood products manufacturing in terms of market opportunities and consumer preferences. A questionnaire was distributed to 30 value-added wood products manufacturers, in which there were 10 manufacturers in each category: door, flooring, and furniture. The study evaluated three aspects: the choice of sawn timber species for particular types of wood products, the source of origin of sawn timber, and the attributes that determined the choice of the sawn timber species for a particular product. The common local sawn timber species include rubberwood, meranti, merpauh, merbau, and kempas species, while poplar, oak, cherry, and pine represent imported species. It was found that cost, supply/availability, product specification, and market/buyer preferences were among the most important factors influencing the selection of sawn timber species for the manufacture of value-added wood products. However, these attributes were not statistically significant among the group of manufacturers and source of origin, respectively.